Pedagogical Beliefs of Arab Mathematics and Religion Teachers in Northern Israel - Chen Goldberg, Chen Goldberg; Ishan, Gamal (Studia Edukacyjne, 2020)
The aim of the current study is to examine the relationship between the pedagogical beliefs of teachers and their profession and to examine how this relationship affects teachers’ self-efficacy perception, satisfaction, and other functional characteristics of the teacher within the educational system. More specifically, the study seeks to compare the pedagogical beliefs of Muslim teachers who teach Religion subjects (i.e. Islamic studies) and the pedagogical beliefs of teachers of secular studies (i.e. Mathematics). According to the proposed research model, the teaching profession (that is, teaching religious Islam or teaching Mathematics) divergently affects the nature of teachers’ pedagogical beliefs, through which they function and perceive their role as teachers. The focus of our study is Arab teachers of Islam versus Arab mathematics teachers, who reflect traditional pedagogical beliefs on two levels, first by selecting teachers belonging to the Muslim minority in Israel, but also in the context of the distinction between teaching. The study hypothesis suggests that there is a difference between the pedagogical beliefs of teachers of Islamic studies and the pedagogical beliefs of Mathematics teachers. In particular, it seeks to examine the claim that teachers of Islamic studies will have a strong traditional belief and weaker constructive belief compared to teachers of secular studies. This research hypothesis has not been confirmed. In fact, except in terms of teachers’ satisfaction, no differences between the two types of teachers were found. This might indicate a change in the Arab society which deviates from the traditional Islamic halakhic approach that focuses almost entirely on religious studies and adopts a more modernized and liberal educational approach, centered on a Western education model and secularism.